PERANAN LEASING SEBAGAI LEMBAGA PEMBIAYAAN PERUSAHAAN - Agnes Maria Janni Widyawati (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
With the increase in economic development increasingly diverse sources of financing are no longer limited to bank credit loans or sources of money and capital markets. In Indonesian financing law, there are various forms of financing institutions, one of which is a leasing or leasing institution according to article 1 of the Joint Decree of the Minister of Finance, Minister of Industry and Minister of Trade No. 122 / MK / IV / 2/1974, No. 32 / M / SK / 2/1974, No. 30 / Kpb / I / 1974 concerning Leasing Business Licensing, what is meant by leasing is: